Data Curation at U.Porto: Identifying current practices across disciplinary domains - Cristina Ribeiro (2011)
The University of Porto is currently concerned with the curation of and the access to the scientific data generated by its researchers. There is a growing awareness of the fragility of digital archives, and researchers feel that they need to keep their data assets alive as the scientific infrastructure becomes more sophisticated. The possibilities of scientific impact derived from open datasets are also becoming evident to them. As a result of an identification task, we present a preliminary study on the datasets which are being used in current research, picking examples from life sciences, engineering, social sciences and arts. The identification also provides insight on current models for data curation, both formal and informal, and on the sensitivity of researchers with respect to open access to their data.